2018
DOI: 10.1016/j.ihj.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Tunisian adults attending primary care physicians (ETHNA-Tunisia)

Abstract: The aim of the Epidemiological Trial of Hypertension in North Africa (ETHNA-Tunisia) was to evaluate the prevalence and clinical profile of hypertension in a large sample of individuals in Tunisia. This was multicenter, epidemiological, cross-sectional study conducted in patients consulting primary care physicians in Tunisia. Mean age of 5802 individuals was 49.6±16.3years. The total prevalence of hypertension was 47.4% (adjusted for age: 26.9%). Control of hypertension was only 37.1%. Hypertension may also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In fact, the national prevalence of hypertension was of 28.7% in 2016 21 . In line with these results, the ETHNA-Tunisia study conducted in the first line among 5802 participants highlighted a hypertension prevalence of 26.9% in men and 28.4% in women 27 . Otherwise, assessment of blood pressures in the visited healthcare facilities was the highest in patients with hypertension or diabetes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In fact, the national prevalence of hypertension was of 28.7% in 2016 21 . In line with these results, the ETHNA-Tunisia study conducted in the first line among 5802 participants highlighted a hypertension prevalence of 26.9% in men and 28.4% in women 27 . Otherwise, assessment of blood pressures in the visited healthcare facilities was the highest in patients with hypertension or diabetes.…”
Section: Discussionsupporting
confidence: 64%
“…Nonetheless, the national prevalence of diabetes was of 15.5% in 2016 21 . The ETHNA-Tunisia study showed a higher prevalence of 19.2% 27 . In the Eastern Mediterranean region, similar prevalences were stated in 2016 (16.2% in Egypt, 13.7% in Libya, and 12.4% in Morocco) 28 .…”
Section: Discussionmentioning
confidence: 94%
“…Among these individuals with hypertension at consultation, 58.2% had a history of hypertension. In addition, when comparing Morocco to other countries of North Africa, Morocco had the lowest prevalence of hypertension among adults ≥ 18 years compared to Tunisia (47.4%) (14) and Algeria (49.5%) (unpublished data). This study showed also a rising overall prevalence of hypertension compared to the study of ministry of health in 2000 that indicates that the prevalence of hypertension in adults is 33.6% (9).…”
Section: Discussionmentioning
confidence: 99%
“…However North‐African population was not well represented in these cohorts. Nevertheless, the management of secondary hypertension in North African patients is challenging because of the higher frequency of essential hypertension and non‐adrenal secondary hypertension in these cohorts compared to other populations [17, 18].…”
Section: Introductionmentioning
confidence: 99%